A direct examination of the dynamics of dipolarization fronts using MMS. Issue 4 (19th April 2017) - Yao, Z. H.; Rae, I. J.; Guo, R. L.; Fazakerley, A. N.; Owen, C. J.; Nakamura, R.; Baumjohann, W.; Watt, C. E. J.; Hwang, K. J.; Giles, B. L.; Russell, C.T.; Torbert, R. B.; et al.
Abstract: Energy conversion on the dipolarization fronts (DFs) has attracted much research attention through the suggestion that intense current densities associated with DFs can modify the more global magnetotail current system. The current structures associated with a DF are at the scale of one to a few ion gyroradii, and their duration is comparable to a spacecraft's spin period. Hence, it is crucial to understand the physical mechanisms of DFs with measurements at a timescale shorter than a spin period. We present a case study whereby we use measurements from the Magnetospheric Multiscale (MMS) Mission, which provides full 3‐D particle distributions with a cadence much shorter than a spin period. We provide a cross validation amongst the current density calculations and examine the assumptions that have been adopted in previous literature using the advantages of MMS mission (i.e., small‐scale tetrahedron and high temporal resolution). We also provide a cross validation on the terms in the generalized Ohm's law using these advantageous measurements. Our results clearly show that the majority of the currents on the DF are contributed by both ion and electron diamagnetic drifts. Our analysis also implies that the ion frozen‐in condition does not hold on the DF, while electron frozen‐in condition likely holds. The new experimental capabilities allow us to accurately calculate Joule heating within the DF, which shows that plasma energy is being converted to magnetic energy in our event. Key Points: We reveal that electrons and ions carry comparable currents on a DF We compared three calculations of current density and show very consistent results Hall MHD is not suitable for DF study, while the electron MHD is likely suitable